2007
DOI: 10.1007/s00702-007-0826-1
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological models of ADHD

Abstract: For more than 50 years, heavy metal exposure during pre- or post-natal ontogeny has been known to produce long-lived hyperactivity in rodents. Global brain injury produced by neonatal hypoxia also produced hyperactivity, as did (mainly) hippocampal injury produced by ontogenetic exposure to X-rays, and (mainly) cerebellar injury produced by the ontogenetic treatments with the antimitotic agent methylazoxymethanol or with polychlorinated biphenyls (PCBs). More recently, ontogenetic exposure to nicotine has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(23 citation statements)
references
References 120 publications
0
22
0
1
Order By: Relevance
“…This 6-OHDA treatment produces a near-ideal model rodent model of severe Parkinson's disease (Kostrzewa et al 2006). Interestingly, neonatally 6-OHDA-lesioned rats have also been established as a model for attention deficit hyperactivity disorder (ADHD), with adulthood hyperactivity being attenuated by acute amphetamine or methylphenidate treatments (Shaywitz et al 1976;Kostrzewa et al 1994Kostrzewa et al , 2007Davids et al 2003). Histamine too (Liu et al 2008) and manganese (Bouchard et al 2007;Farias et al 2010) also have demonstrated roles in ADHD animal modeling.…”
Section: Discussionmentioning
confidence: 96%
“…This 6-OHDA treatment produces a near-ideal model rodent model of severe Parkinson's disease (Kostrzewa et al 2006). Interestingly, neonatally 6-OHDA-lesioned rats have also been established as a model for attention deficit hyperactivity disorder (ADHD), with adulthood hyperactivity being attenuated by acute amphetamine or methylphenidate treatments (Shaywitz et al 1976;Kostrzewa et al 1994Kostrzewa et al , 2007Davids et al 2003). Histamine too (Liu et al 2008) and manganese (Bouchard et al 2007;Farias et al 2010) also have demonstrated roles in ADHD animal modeling.…”
Section: Discussionmentioning
confidence: 96%
“…Several animal models of ADHD have been proposed (for review see also Kostrzewa et al 2008;Russell et al 2005;Sagvolden et al 2005;van der Kooij and Glennon 2007), and most of these models were initially based on the presence of hyperactivity. However, face validity of an animal model of ADHD should also include impulsive behaviour and attention deficits.…”
Section: Discussionmentioning
confidence: 99%
“…Children who have suffered a brain injury may show some behaviours similar to those of ADHD (Kostrzewa et al 2008). However, this is not likely to be a primary reason because only a small percentage of children with ADHD have suffered a traumatic brain injury.…”
Section: Brain Injuriesmentioning
confidence: 98%